2017
DOI: 10.1155/2017/7807313
|View full text |Cite
|
Sign up to set email alerts
|

Natural Modulators of Endosomal Toll-Like Receptor-Mediated Psoriatic Skin Inflammation

Abstract: Psoriasis is a chronic inflammatory autoimmune disease that can be initiated by excessive activation of endosomal toll-like receptors (TLRs), particularly TLR7, TLR8, and TLR9. Therefore, inhibitors of endosomal TLR activation are being investigated for their ability to treat this disease. The currently approved biological drugs adalimumab, etanercept, infliximab, ustekinumab, ixekizumab, and secukizumab are antibodies against effector cytokines that participate in the initiation and development of psoriasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 174 publications
(118 reference statements)
0
57
0
1
Order By: Relevance
“…24,37 The research on molecular targets and mechanisms of natural products has greatly contributed to the progress in the treatment of skin diseases. 38 Our results clearly show that GL exhibits cellular inhibitory mechanisms in the IMQ-induced psoriasis-like mouse model and could be a candidate natural modulator for psoriasis. Importantly, the doses we applied in this study have also been used in the human prostate xenograft tumor model 13 and the allergic contact hypersensitivity model 14 with no detectable toxicity in mice, indicating the safety of GL application.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…24,37 The research on molecular targets and mechanisms of natural products has greatly contributed to the progress in the treatment of skin diseases. 38 Our results clearly show that GL exhibits cellular inhibitory mechanisms in the IMQ-induced psoriasis-like mouse model and could be a candidate natural modulator for psoriasis. Importantly, the doses we applied in this study have also been used in the human prostate xenograft tumor model 13 and the allergic contact hypersensitivity model 14 with no detectable toxicity in mice, indicating the safety of GL application.…”
Section: Discussionmentioning
confidence: 54%
“…A large number of botanicals have been studied for the treatment of psoriasis . The research on molecular targets and mechanisms of natural products has greatly contributed to the progress in the treatment of skin diseases . Our results clearly show that GL exhibits cellular inhibitory mechanisms in the IMQ‐induced psoriasis‐like mouse model and could be a candidate natural modulator for psoriasis.…”
Section: Discussionmentioning
confidence: 63%
“…Scientific literature show that in autoimmune diseases, such as lupus and psoriasis, TLRs 7 and 8 recognize endogenous immune complexes (IC) containing nucleic acids, and induce proinflammatory cytokines contributing to the progression of the disease [273,286].…”
Section: Implications In Autoimmune Diseasesmentioning
confidence: 99%
“…IMO-3100, dual antagonist of TLR7 and TLR9, is being tested for the treatment of inflammatory and autoimmune disease, such as SLE, rheumatoid arthritis, multiple sclerosis, psoriasis, lupus and colitis. Evaluation of the effect of IMO-3100 on gene expression in human peripheral blood monocytes showed that the drug could significantly reduce the expression of inflammatory genes, such as IL-17A, b-defensin, CXCL1, and keratin 16, inhibited TLR ligandinduced expression of TNF-a and IFNa [286,347,351].…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…Forsbach observed that the activation of TLR-8 led to the secretion of inflammatory cytokines such as IFN-γ, TNF-α and IL-12 (Ospelt and Gay 2010). Moreover, the accumulating evidence indicates that CPG-52364 as TLR antagonist, could block several inflammatory autoimmune diseases induced by activation of TLR7, TLR8 and TLR9 in clinical trials (Lai et al 2017). It meant that TLR8 was associated with systemic inflammation, which was involved in pathophysiology of PCOS.…”
mentioning
confidence: 99%